2005
DOI: 10.3200/mono.131.2.77-127
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Academic Support From Parents, Teachers, and Peers to Hong Kong Adolescents' Academic Achievement: The Mediating Role of Academic Engagement

Abstract: The author tested a model hypothesizing that students' self-perceived academic support (from parents, teachers, and peers) is related to their achievement directly and indirectly through their own perceived academic engagement. The participants were 270 adolescents (M age = 15.41 years, range = 14-20 years) from 3 grade levels (Forms 3-5, equivalent to Grades 9-11 in the United States) in a Hong Kong secondary school. The school principal and teachers helped to collect data based on these adolescents' response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
161
1
28

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(203 citation statements)
references
References 81 publications
13
161
1
28
Order By: Relevance
“…However, few studies have examined all the three supports in a single study. Chen (2005) is a rare exception in this respect. Examining data from 270 Hong Kong adolescents, Chen found that the effects of these three contextual factors on academic achievement were mediated partially by student engagement.…”
Section: Contextual Antecedentsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, few studies have examined all the three supports in a single study. Chen (2005) is a rare exception in this respect. Examining data from 270 Hong Kong adolescents, Chen found that the effects of these three contextual factors on academic achievement were mediated partially by student engagement.…”
Section: Contextual Antecedentsmentioning
confidence: 99%
“…That is, student engagement was the mediator in the relations between the three contextual factors and academic achievement. However, gender differences were not examined in Chen (2005). To increase educators' understanding of the gender gap in academic achievement, it is important to explore whether this partial mediation model could be replicated for both genders across countries.…”
Section: Contextual Antecedentsmentioning
confidence: 99%
See 3 more Smart Citations